2010
DOI: 10.1089/jwh.2009.1845
|View full text |Cite
|
Sign up to set email alerts
|

Family Violence Exposure and Health Outcomes Among Older African American Women: Do Spirituality and Social Support Play Protective Roles?

Abstract: Spirituality and social support are two potentially modifiable determinants of health for older African American women. Culturally appropriate mechanisms to enhance social support and spirituality levels need to be explored as potential inteventions to improve the health of those African American women who have been exposed to FV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 34 publications
2
37
0
3
Order By: Relevance
“…Social support has been shown in other studies to directly aid families in maintaining stable employment, increasing their education level, increasing job skills training, and buffering against physical and mental health limitations (Carlton et al, 2006;Corcoran, 1995;Dominguez & Watkins, 2003;Jackson et al, 2000;Lin et al, 2009;Paranjape & Kaslow, 2010). The results of this DFA, when considered with previous resilience research, provide exceedingly strong evidence that Downloaded by [Erciyes University] at 07:34 26 December 2014 social support, as a component of resilience, is indeed a necessary prerequisite to socioeconomic mobility (AUTHORS, 2013;Johnson et al, 2011;Keene & Geronimus, 2011;Tester et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support has been shown in other studies to directly aid families in maintaining stable employment, increasing their education level, increasing job skills training, and buffering against physical and mental health limitations (Carlton et al, 2006;Corcoran, 1995;Dominguez & Watkins, 2003;Jackson et al, 2000;Lin et al, 2009;Paranjape & Kaslow, 2010). The results of this DFA, when considered with previous resilience research, provide exceedingly strong evidence that Downloaded by [Erciyes University] at 07:34 26 December 2014 social support, as a component of resilience, is indeed a necessary prerequisite to socioeconomic mobility (AUTHORS, 2013;Johnson et al, 2011;Keene & Geronimus, 2011;Tester et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a family's level of social support increases, it directly aids the family in (1) maintaining stable employment, (2) receiving adequate housing, (3) increasing education, (4) increasing job skills training, and (5) buffering against physical and mental health limitations (Carlton et al, 2006;Corcoran, 1995;Dominguez & Watkins, 2003;Jackson, Brooks-Gunn, Huang, & Glassman, 2000;Lin, Thompson, & Kaslow, 2009;Paranjape & Kaslow, 2010). However, as pointed out by Distelberg and Taylor (2013), social support alone is not enough.…”
Section: Factors Affecting Family Resilience and Employmentmentioning
confidence: 99%
“…Spirituality is a critical resource that can serve a protective function against a range of negative outcomes (Paranjape & Kaslow, 2010; Yonker, Schnabelrauch, & DeHaan, 2012). Especially for the low-income African American women in the study, spirituality represents a non-financial resource with important implications for parenting (Cain, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In some articles, researchers included other study samples as well, but in these studies, the researchers reported results specifically from older women who experienced IPV. We excluded some studies because, although the sample included older women who experienced intimate partner violence, other types of abusers were also included, and data from older women abused by intimate partners were not examined independently (i.e., Paranjape & Kaslow, 2010). The research reviewed was limited to English-language reports of research, and we found articles reporting research conducted in Australia, Canada, Israel, the United States, and Europe, which reflect the areas where most of the services, supports, and advocacy groups for older abused women can be found (Hightower et al, 2006).…”
Section: Methodsmentioning
confidence: 99%